2010
DOI: 10.1111/j.1365-3040.2010.02232.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycinebetaine protects plants against abiotic stress: mechanisms and biotechnological applications

Abstract: Various compatible solutes enable plants to tolerate abiotic stress, and glycinebetaine (GB) is one of the most-studied among such solutes. Early research on GB focused on the maintenance of cellular osmotic potential in plant cells. Subsequent genetically engineered synthesis of GBbiosynthetic enzymes and studies of transgenic plants demonstrated that accumulation of GB increases tolerance of plants to various abiotic stresses at all stages of their life cycle. Such GB-accumulating plants exhibit various adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
361
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 611 publications
(372 citation statements)
references
References 131 publications
(217 reference statements)
8
361
3
Order By: Relevance
“…Titration. All experiments were performed in the presence of betaine, a natural osmolyte, at pH 7.0, because it has previously been shown that PS II preparations are more stable in the presence of 1 M glycine betaine (12,(38)(39)(40)(41)(42)(43). Details of the physiological conditions used for various species are summarized in SI Materials and Methods, Figs.…”
Section: Methodsmentioning
confidence: 99%
“…Titration. All experiments were performed in the presence of betaine, a natural osmolyte, at pH 7.0, because it has previously been shown that PS II preparations are more stable in the presence of 1 M glycine betaine (12,(38)(39)(40)(41)(42)(43). Details of the physiological conditions used for various species are summarized in SI Materials and Methods, Figs.…”
Section: Methodsmentioning
confidence: 99%
“…GB is one of the most studied compatible compound for abiotic stress tolerance due to its versatile function. Several studies have shown that level of GB is increased in naturally accumulating plants under stressful conditions [3]. It also protects plants against various stresses and also protects quaternary structure of proteins, various enzymes and other macromolecules involved in disease protection [4].…”
Section: Introductionmentioning
confidence: 99%
“…(A) This pathway, which is encoded by a DNGP, produces a reactive toxic IC, betaine aldehyde, during the conversion of choline to betaine. Betaine can reach high concentrations during osmotic stress, an indication of substantial flux that must be regulated to match environmental conditions (48). Betaine aldehyde toxicity is indicated by its use as an alternative to antibiotics for selection of transformants in plant species that lack the pathway (22).…”
Section: Phytophthora Infestansmentioning
confidence: 99%